A Sociological Review of the 2020 Regional Election Budget Preparation in Jember Regency: A Case Study of the KPU Jember - Rahmat, Agus Zainur; Putra, Hendrawan Santosa; Prasetyo, Whedy (International Journal of Business and Applied Economics, 2024)
This study analyzes the budgeting process from a sociological perspective, linking it to the phenomena observed during the 2020 simultaneous regional elections at KPU Jember. Using Institutional Isomorphism Theory, the research explores how these phenomena are reflected in the budgeting process. A qualitative approach with a case study methodology was employed, with data collected through interviews with key actors involved in the preparation of the 2020 regional election budget in Jember Regency. The analysis reveals that three mechanisms of institutional isomorphism (mimetic, coercive, and normative) were evident in the budgeting process. The findings demonstrate that sociological factors are integral to the budgeting process, as shown by the application of these isomorphism mechanisms at KPU Jember.